Attitudes of Palestinian and Polish Medical Students Towards Death. (November 2022) - Zdziarski, Krzysztof; Awad, Mariam S.; Landowski, Marek; Zabielska, Paulina; Karakiewicz, Beata
Attitudes of students of health-related subjects towards the death are an important issue showing the behaviour and values ​​that guide young people in everyday interactions. The study was conducted using the Questionnaire About Attitudes Against Death (DAP-R-PL) among 309 students, including 150 Palestinian from the Faculty of Nursing and Health Sciences and 159 Polish from the Faculty of Health Sciences. It was noticed that the attitude of Death Avoidance is higher in Palestinians than in Poles. The biggest difference between correlation indicators is for the factors fear of death and death avoidance (FD and DA). This value is positive for Palestinian respondents and negative for Polish respondents. The study confirms that the attitudes of students towards death from both universities in the perspective of 5 factors are positive and in future contacts with dying patients they will cope with this challenge.